Does Hypofractionated Radiotherapy Regimens Increase the Vulnerability to SARS- COV-2 by Influencing ACE-2 Activity? - Cherkaoui, Ghofrane S.; Taleb, Sara; Kadil, Youness; Filali, Houda (Coronaviruses, 2021)
In the context of the novel Coronavirus pandemic due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the management of patients with cancer constitutes a real challenge. These patients are more likely to be immunocompromised due to the underlying malignancy or anticancer treatments. As a consequence, they are more at risk of contracting this virus and tend to show a higher rate of fatal cases. In order to reduce the risk of this pandemic among patients and health care professionals, oncologists are currently proposing hypofractionated radiotherapy regimens using higher doses per fraction, thus shortening treatment courses and saving treatment visits. Since higher doses of radiation may also increase the ACE/ACE2 activity, which has been identified as a key SARS-CoV-2 receptor, this paper raises the question of whether hypofractionated radiotherapy regimens further increase the infectivity of these already vulnerable patients.
Keywords: SARS CoV 2